Time-course assessment of 3D-image distortion on the 1.5 T Marlin/Elekta Unity MR-LINAC. (August 2022) - Damyanovich, Andrei Z.; Tadic, Tony; Foltz, Warren D.; Jelveh, Salomeh; Bissonnette, Jean-Pierre
Highlights: We assessed the temporal stability of image distortion on a 1.5 T MR-LINAC. Distortion was evaluated over 200 – 500 mm DSVs via 76 weekly measurements. Time-average absolute ('total') distortion dr ≤ 1 mm for DSVs ≤ 300 mm. dr ≤ 1.5 mm for DSV 400 mm and ≤ 2.5 mm for DSV 500 mm. Total distortion on the MR-LINAC was stable across the 18-month evaluation period. Image distortion may change following gradient servicing and should be monitored. Abstract: Purpose: The efficacy of MR-guided radiotherapy on a MR-LINAC (MR-L) is dependent on the geometric accuracy of its MR images over clinically relevant Fields-of-View (FOVs). Our objectives were to: evaluate gradient non-linearity (GNL) on the Elekta Unity MR-L across time via 76 weekly measurements of 3D-distortion over concentrically larger diameter spherical volumes (DSVs); quantify distortion measurement error; and assess the temporal stability of spatial distortion using statistical process control (SPC). Methods: MR-image distortion was assessed using a large-FOV 3D-phantom containing 1932 markers embedded in seven parallel plates, spaced 25 mm × 25 mm in- and 55 mm through-plane. Automatically analyzed T1 images yielded distortions in 200, 300, 400 and 500 mm concentric DSVs. Distortion measurement error was evaluated using median absolute difference analysis of imaging repeatability tests. Results: Over the measurement period absolute time-averaged distortion varied between: dr = 0.30 – 0.49 mm, 0.53 – 0.80 mm, 1.0 – 1.4 mm and 2.28 – 2.37 mm, for DSVs 200, 300, 400 and 500 mm at the 98 th percentile level. Repeatability tests showed that imaging/repositioning introduces negligible error: mean ≤ 0.02 mm (max ≤ 0.3 mm). SPC analysis showed image distortion was stable across all DSVs; however, noticeable changes in GNL were observed following servicing at the one-year mark. Conclusions: Image distortion on the MR-L is in the sub-millimeter range for DSVs ≤ 300 mm and stable across time, with SPC analysis indicating all measurements remain within control for each DSV.